A randomised controlled trial of laser scanning and casting for the construction of ankle–foot orthoses. (April 2016) - Roberts, Andrew; Wales, Johanna; Smith, Heather; Sampson, Christopher James; Jones, Peter; James, Marilyn
Background: Three-dimensional laser scanning has been used for patient measurement for cranial helmets and spinal braces. Ankle–foot orthoses are commonly prescribed for children with orthopaedic conditions. This trial sought to compare ankle–foot orthoses produced by laser scanning or traditional plaster casting. Objectives: Assessment of the effectiveness and efficiency of using laser scanning to produce ankle–foot orthoses. Study design: Randomised controlled trial with blinding of orthotists and patients to the construction technique used. Methods: A randomised double-blind trial comparing fabrication of ankle–foot orthoses from casts or laser scans. Results: The time spent in the rectification and moulding of scanned ankle–foot orthoses was around 50% less than for cast ankle–foot orthoses. A non-significant increase of 9 days was seen in the time to delivery to the patient for laser scanning with computer-aided design and computer-aided manufacturing. There was a higher incidence of problems with the scan-based ankle–foot orthoses at delivery of the device, but no difference in how long the ankle–foot orthoses lasted. Costs associated with laser scanning were not significantly different from traditional methods of ankle–foot orthosis manufacture. Conclusion: Compared with conventional casting techniques, laser scan–based ankle–foot orthosis manufacture did not significantly improve either the quality of the final product or the time to delivery. Clinical relevance: Ankle–foot orthoses (AFOs) are a common requirement for chronic neurological conditions during childhood. Improved efficiency of provision of AFOs would benefit children and families by reducing the delay in provision of devices and would benefit the health service by making best use of valuable orthotist time.